ANALISIS PERSAINGAN EKONOMI ANTAR PEDAGANG PEREMPUAN PENJUAL SAYUR DI PASAR RAKYAT FLAMBOYAN PONTIANAK - Novianty, Ira; Sulistyarini, Sulistyarini; Fatmawati, Fatmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to find out about "Economic Competition among Women Traders of Vegetable Traders in Pontianak Flamboyant People's Market" The research method used is descriptive with a form of qualitative research. The source of the data of this research is the women traders of vegetable sellers in Pontianak Flamboyan People's Market and the data are data sheets provided by the Pontianak City SME trade office as well as the results of interviews with women traders selling vegetables in Pontianak Flamboyan People's Market. The analysis in this study was presented in a descriptive qualitative manner using 4 informants. 1. How do traders improve the quality of vegetable products in the Pontianak Flamboyan people's market? 2. How do traders reduce the price of vegetable products in the Pontianak Flamboyan people's market? The results showed that 1 economic competition based on product quality has a strong competitiveness towards consumer choices 2. Price pressure by looking at the quality of products that are getting better then it has a higher selling value so that competition with selling prices will be higher.            Keywords: Competition, Economy, Women Traders